Negotiation of Objects in Urban Kampong Street: A Case Study in Ampiun Alley, Cikini - Winda Hutami Tatyana; Joko Adianto; Rossa Turpuk Gabe (International Journal of Built Environment and Scientific Research, 2019)
This paper aims to explore objects in the street of urban kampong, in order to understand the social system and the spatial mechanism of the objects. Existence of objects and their formation are physical trails of social activities. The role of object in social engagement can affect the street space and the behaviour of its users. In urban kampong street, objects engaging in social activities mainly in spatial negotiation. The case study was taken in Ampiun Alley of Kampong Cikini, one of the most dense settlement in Central Jakarta. It was studied through observations, documentations, mapping, and interviews. In Ampiun Alley, various objects from transportation to domestic tools exist on the alley, while many passer-bys going through it. They were able to be tolerated because it did not give disadvantages to the street community, did not being an obstacle in circulation, and did not give a slum-like image. We have discovered there are many different negotiation spaces produced following surrounding social condition and space needs. However, in general formation of objects was shaped through toleration and consensus activities, so it could avoid any possible conflict and maintain the main function of the alley itself.